Pregnancy outcomes in sexually transmitted infections or human immunodeficiency viruses infected women at a tertiary care center: a retrospective study - K. P., Saradha; Stephen, Anitha Christy; Huddar, Vikram V. (International Journal of Research in Dermatology, 2021)
Background: The natural history of HIV infection in early disease is not affected by pregnancy. In later stages there may be rapid disease progression leading to adverse pregnancy outcomes. Prevalence of HIV in India is 0.3% in pregnant women. With the advent of PPTCT, there have been a decline in the adverse pregnancy outcomes but still few adversities are reported. Aim of the study was to assess the various pregnancy outcomes in HIV positive women and the effects of antiretroviral therapy (ART). Methods: A retrospective analytical study conducted from July 2017-June 2019 on HIV infected pregnant women. Their maternal age, CD4 count at diagnosis of HIV, after postpartum, mode of delivery, birth weight and HIV status of baby were noted and analyzed. Results: 18 HIV infected pregnant women were included. Their mean age was 25.6 years. 12 patients were in 2nd trimester and the rest in 1st trimester. All were on triple-drug (TEL) regimen. Three were diagnosed with HIV prior to conception and were already on ART. Remaining were detected at the time of ANC visit. All cases fall under stage I WHO clinical staging. Out of the 18 pregnant, two delivered by LSCS and the rest by normal delivery. All were term deliveries, with mean birth weight of 2.82 kg. One HIV infected baby was born by LSCS. The mean CD4 count at the time of diagnosis of HIV was 389 and at postpartum was 508. Overall, there was seen to be an increase in CD4 count without any adverse effects during ART. Conclusions: Prompt HIV diagnosis and ART initiation during antenatal period can have good pregnancy outcome and thereby reducing transmission to children.